The value of prostatic acid phosphatase and prostate specific antigen as serum markers in carcinoma of the prostate - (:unkn) unknown (My University, 1993)
The value of prostatic acid phosphatase (PAP) and prostate specific antigen (PSA) as serum markers in carcinoma of the prostate (CaP) was investigated in this study. A group of 75 patients entered this trial, 25 with CaP, 25 with benign prostatic hyperplasia (BPH) and 25 with urologic disorders other than prostatic diseases. In the CaP group, PAP was above normal levels in 48% of the patients and PSA in 92%. In the BPH group these rates were 20% and 72%, respectively. No elevation was detected in the third group. In CaP patients with capsular invasion, PAP and PSA levels were above normal in 25 and 87.5%. In metastatic carcinoma, PAP was high in 75% and PSA in 100%. Our study reveals that neither of these markers is useful in the initial diagnosis of CaP. Though PSA seems to be more sensitive, it is not more specific than PAP.
Keywords: Humans; Middle Aged; Biomarkers, Tumor; Aged; Aged, 80 and over; Male; Prostatic Neoplasms; Urologic Diseases; Acid Phosphatase; Prostate; Prostate-Specific Antigen; Prostatic Hyperplasia